Museum Education for Children with Disabilities: Development of the Nature Senses Traveling Trunk. (2nd July 2016) - Cho, Hyojung; Jolley, Anna
ABSTRACT: Since museums are cultural, educational, and social institutions, providing access to people with disabilities has increased in recent decades. This research examines the need and development process of the educational program, the Nature Senses Traveling Trunk, to serve children with Autism Spectrum disorders and visual impairments at the Lubbock Lake National Historic Landmark. The case study is shared not only to raise awareness for serving people with disabilities, but also to encourage museum professionals to put those ideas into action. The research emphasizes the collaboration with diverse stakeholders and communication with museum audiences to ensure the quality of such special education programs.